Peritoneal vegetable foreign body (Indian Journal of Case Reports, 2020)
Insertion of foreign bodies in the rectum for sexual pleasure is quite common, especially in homosexual males, but their presentation with rectal perforation leading to fecal peritonitis and the whole object lying in the right iliac fossa (intraperitoneally) is rare. We report a rare case where a 45-year-old male presented with an acute abdomen with no other history, which on exploration turned out to be a large 10? long brinjal (vegetable) lying in the right iliac fossa adjacent to the ascending colon, with fecal peritonitis. The rationale for reporting this case is the unusual presentation and unexpected surprising findings on exploration. No one would ever expect brinjal lying in the usual location of the appendix, on exploring a case of fecal peritonitis.